2018
DOI: 10.1111/jan.13550
|View full text |Cite
|
Sign up to set email alerts
|

An umbrella review of clinical practice guidelines for the management of patients with hip fractures and a synthesis of recommendations for the pre‐operative period

Abstract: Results of this review illustrate that not all practice guidelines are of equal quality. Given the costs associated with the development and maintenance of high-quality practice guidelines, such work may be more efficiently completed through international collaborations and then adapted for national and regional healthcare contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…First, the multi-phased search strategy that includes searching bibliographic databases, CPG library databases, as well as the grey literature was developed with the support of a health science librarian. CPGs are typically not well indexed in bibliographic databases [ 36 , 39 , 64 ], therefore developing and conducting this extensive search strategy will mitigate this issue. Second, building on Johnston et al’s (2019) methodological guidance [ 36 ], our team has developed a manual to train and support study team members during each of the literature screening, critical appraisals, and data abstraction and synthesis stages of the research.…”
Section: Discussionmentioning
confidence: 99%
“…First, the multi-phased search strategy that includes searching bibliographic databases, CPG library databases, as well as the grey literature was developed with the support of a health science librarian. CPGs are typically not well indexed in bibliographic databases [ 36 , 39 , 64 ], therefore developing and conducting this extensive search strategy will mitigate this issue. Second, building on Johnston et al’s (2019) methodological guidance [ 36 ], our team has developed a manual to train and support study team members during each of the literature screening, critical appraisals, and data abstraction and synthesis stages of the research.…”
Section: Discussionmentioning
confidence: 99%
“…An ultrasound-guided femoral nerve block is a valuable alternative to systemic analgesic in hip fracture patients as it provides analgesia to the fractured area, thereby facilitating reduction in systemic opioid administration [18]. Providing optimal pain control in hip fracture patients requires advanced nursing and physician care due to comorbidity [19][20][21]. Tus, optimizing acute pain assessment and management is important.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that patients with hip fractures receive the best possible care and to facilitate patients' discharge in a condition relative to their prefracture condition, certain care standards related to aspects of pre‐, intra‐ and postoperative management should be followed. In general, pre‐operative management includes timing of surgery, expedited patient management, identification and treatment of correctable comorbidities, pain management, preventive measures and multidisciplinary management (Filiatreault, Hodgins, & Witherspoon, ). In a review, Farrow et al () concluded that low compliance to care standards is associated with increased mortality, reduced likelihood of a short length of stay and increased odds of discharge to a high‐care setting (Farrow et al, ).…”
Section: Introductionmentioning
confidence: 99%